Interparental Conflict and Academic Performance in Chinese High School Students: A Serial Mediation Model - Xiong, Mingrui; Liu, Qian; He, Yunfeng (Psychology in the schools, 2025)
ABSTRACT Previous research indicates that students' academic performance can be negatively affected by interparental conflict. However, studies focusing on Chinese high school students, whose academic performance is particularly emphasized, are limited. Moreover, relatively little work has examined the mechanisms underlying the association between interparental conflict and academic performance. Based on the cognitive‐contextual framework and expectancy‐value theory, the current study explored the potential cognitive mediators between interparental conflict and academic performance in 748 Chinese high school students with a mean age of 17.07 years. The results revealed a significant negative relationship between interparental conflict and academic performance, and further showed that academic self‐efficacy mediated the association between interparental conflict and academic performance. Additionally, all components of cognitive appraisals and academic self‐efficacy demonstrated a serial mediation effect on the relationship between interparental conflict and academic performance. Therefore, concerning youth academic outcomes, these findings highlight the need for a greater focus on students' belief in learning ability and also their cognitive reactions towards interparental conflict. Summary Interparental conflict is negatively associated with academic performance among Chinese high school students. Academic self‐efficacy serves as a mediator in the relationship between interparental conflict and academic performance. The serial mediation effect of cognitive appraisals and academic self‐efficacy further elucidates the relationship between interparental conflict and academic performance.